The mandate and operational approach of the Asia – Pacific Economic Cooperation - Yong, Zhou (Journal of the Belarusian State University. International Relations, 2025)
Established in 1989, the Asia – Pacific Economic Cooperation (APEC) facilitates economic cooperation and integration among its 21 member economies. Unlike other regional international organisations, APEC employs a consensus-driven, non-binding framework. Nevertheless, it effectively advances regional free trade. This paper examines APEC’s mandate and competence, contrasting its voluntary approach with the binding frameworks of organisations like the EU and ASEAN. It argues that APEC’s efficacy derives from its flexibility, reliance on voluntary action plans, and use of soft law instruments, which support regional alignment while respecting national sovereignty. The paper concludes that institutionalising capacitybuilding initiatives, particularly in domains such as digital trade and environmental sustainability, could strengthen APEC’s ability to respond to contemporary economic challenges without resorting to binding commitments.